Monitoring Phthalates in Maternal and Cord Blood: Implications for Prenatal Exposure and Birth Outcomes. (23rd February 2022) - Hwa, Hsiao‐Lin; Peng, Fu‐Shiang; Ting, Te‐Tien; Chen, Huei‐Wen; Chan, Hsiang‐Yu; Yang, Da‐Peng; Chen, Pau‐Chung; Kuo, Yun‐Ning; Chen, Pai‐Shan
Abstract: Although many phthalates are endocrine‐disrupting chemicals that are associated with adverse birth outcomes, the relationship between maternal phthalate exposure and birth outcomes is not yet conclusive. The objective of the present study was to investigate the association between prenatal exposure to phthalates in human maternal and cord blood and birth outcomes of the infants. Sixty‐five mother–infant pairs were recruited in Taipei City and New Taipei City, and birth outcomes of the infants were recorded. Twelve phthalate metabolites were measured in maternal and cord blood samples. The mean of mono‐ethyl phthalate, mono‐isobutyl phthalate (MiBP), mono‐ n ‐butyl phthalate (MnBP), and mono‐(2‐ethylhexyl) phthalate (MEHP) was relatively higher than that of the other metabolites in both maternal and infant blood. There was a significant difference ( p < 0.05) for mono‐methyl phthalate (MMP) and MnBP between the maternal blood and cord blood of male infants. Mono‐benzyl phthalate (MBzP), MMP, MiBP, and ∑di‐2‐ethylhexyl phthalate (∑DEHP) in maternal blood were inversely correlated with the anogenital index (AGI) of male infants, with a p value between 0.011 and 0.033. Mono‐ n ‐octyl phthalate, MMP, MiBP, MnBP, and MBzP were positively correlated with the AGI of female infants, with a p value between 0.001 and 0.034. Cord blood levels of MnBP, mono‐(2‐ethyl‐5‐oxohexyl)‐phthalate, MEHP, and ∑DEHP were found to be inversely associated with head circumference in all the infants, adjusted for gestational age. Phthalate monoesters are potentially estrogenic and antiandrogenic chemicals. Longitudinal follow‐up of the present study population could help clarify the long‐term impact of phthalates on growth and the health effects of background exposure levels. Environ Toxicol Chem 2022;41:715–725. © 2022 SETAC Abstract : Monitoring phthalates in maternal and cord blood for birth outcomes.